2015
DOI: 10.1007/978-3-319-14033-9_6
|View full text |Cite
|
Sign up to set email alerts
|

Biogas from Lignocellulosic Materials

Abstract: Methane production via anaerobic digestion is a steadily growing industry in Europe and all over the world. Biomethane reduces the demand for fossil fuels, since it can be used for the production of power and heat or converted to vehicle fuel. Anaerobic digestion is a renewable energy technology; however, it can also be considered as a low-cost environmental-friendly waste management process, since it reduces the emission of greenhouse gases (GHGs), while it stabilizes the wastes. Currently, mainly the organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 160 publications
(159 reference statements)
0
10
0
Order By: Relevance
“…An analysis of the enzymatic activity would also offer an elegant way to better evaluate the effects of TE addition on the activity of the microbial enzymes, including cellulases that are responsible for the hydrolysis of the cellulose contained in the rice straw [41]. Zhang et al [42] and Tian et al [43] showed a positive effect of Fe and Ni in enhancing the biogas production yields from cow dung and Phragmites straw, respectively, ascribing this also to a stimulation of the cellulase activity.…”
Section: Effect Of Fe and Co Addition On Biomethane Production And Vfmentioning
confidence: 99%
“…An analysis of the enzymatic activity would also offer an elegant way to better evaluate the effects of TE addition on the activity of the microbial enzymes, including cellulases that are responsible for the hydrolysis of the cellulose contained in the rice straw [41]. Zhang et al [42] and Tian et al [43] showed a positive effect of Fe and Ni in enhancing the biogas production yields from cow dung and Phragmites straw, respectively, ascribing this also to a stimulation of the cellulase activity.…”
Section: Effect Of Fe and Co Addition On Biomethane Production And Vfmentioning
confidence: 99%
“…To date, the attempts aimed at investigating the effects of different pretreatment processes on AD were only focused on substrate characteristics [16]. In other words, so far the impacts of pretreatments on AD of lignocelluloses has only been investigated by taking into consideration the changes in main substrate properties, including composition, surface properties, crystallinity, the degree of polymerization (DP), enzymes adsorption/desorption, and accessibility [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the optimal C/N ratio for anaerobic co-digestion of peanut hulls and swine manure may be determined by the types of biogas materials and is not possibly unified in a specific range. Because most of the biogas materials are organic wastes, the peanut hull used in this experiment is rich in recalcitrant components, such as lignocellulose (semicellulose, cellulose, and lignin), which have been proven to be hard to be utilized by anaerobic organisms in a short retention time without any special pretreatments . Hence, a large amount of “invalid carbon” existing in these materials is also included in the calculation of C/N.…”
Section: Discussionmentioning
confidence: 99%
“…Because most of the biogas materials are organic wastes, the peanut hull used in this experiment is rich in recalcitrant components, such as lignocellulose (semicellulose, cellulose, and lignin), which have been proven to be hard to be utilized by anaerobic organisms in a short retention time without any special pretreatments. 29 Hence, a large amount of "invalid carbon" existing in these materials is also included in the calculation of C/N. Thus, to be more exact, this C/N ratio should be called total C/N, which can present only the general characteristics of the biogas material but cannot indicate accurately the properties of the substrate that can be actually utilized by anaerobic organisms.…”
Section: Validation Of the Optimal Parametersmentioning
confidence: 99%